Impact of Motor Vehicle Emissions on Air Quality in Urban and Sub Urban Area - A. Ikhsan Karim; Sugito SUGITO (International Conference on Engineering and Technology Development (ICETD), 2014)
One of the effects of development and growth in urban areas is the increasing number of vehicles from year to year . Improved transportation needs to support the activities of the community , the problems faced by large cities today . Along with these problems , the most crucial in the presence of the number of vehicles is the problem of congestion .Vehicle congestion and concentrated on a spot will cause air pollution . Air pollution comes from motor vehicle exhaust emissions contain toxic substances that are harmful to human health , among others , CO, HC, CO2, SOx, NOx, PM10 .JICA study said 70 % of air pollution occurs in urban contributed from motor vehicles , and the remaining 30% are caused by industrial and household activities .Based on these facts , the government sought to continue to make prevention of air pollution in accordance with the mandate of Law No. 32/2009 about Protection and Management of the Environment and Government Regulation No. 41/1999 about Air Pollution Control. In addition , more specific regulation No.5/MENLH/2006 , regulates the Threshold Motor Vehicle Exhaust Emissions that can be used as a legal basis so that exhaust emissions from motor vehicles do not pollute the air . Air pollution control efforts are primarily aimed at improving air quality for human life.Referring to the importance of the above issues , this study will examine the effect of vehicle emissions on air quality in Urban and Sub- Urban areas in the city of Bandar Lampung.This study uses primary and secondary data , which begins with a review of the concept of the development of Bandar Lampung city transport system , then analysis the influence of motor vehicle exhaust emissions , especially gas CO , SO2 and NO2 air quality in urban and sub-urban aras.The results of this study will show how much influence the motor vehicle exhaust emissions on ambient air quality in urban and sub-urban areas . It is expected Bandar Lampung city government can adopt policies to reduce air pollution from transportation Activities.